Ocean outpost the future of humans living underwater - Seedhouse, Erik (Springer New York, 2011)
Ocean Outpost is an undersea roadmap charting the future of humankind's exploration of Earth's last vast unexplored territory. To realize the goal of an extended human presence underwater a wealth of new technologies will be developed, such as new manned and unmanned submersibles, advanced propulsion systems, underwater rescue systems, decompression methods, and revolutionary physiological intevention strategies ranging from liquid ventilation to artificial gills. Some techonologies will require quantum leaps forward in innovation, while others may appear even more daunting.